Sustainable assessment of learning experiences based on projects - Ignacio TRAVERSO RIBÓN; Antonio BANDERAS ALBERICO; Juan Manuel DODERO; Iván RUIZ RUBE; Manuel PALOMO (Ediciones Universidad de Salamanca, 2016)
In a project-based learning experience, the detailed monitoring of the activities in which team members participate can be useful to evaluate their work. Using learning-oriented assessment procedures, supervisors can assess the teamwork abilities with a formative purpose. Evaluation strategies such as self-assessment, peer assessment and co-assessment are often used to make evaluation formative and sustainable. Conducting an assessment strategy is not easy for team members, since they need before to have a reasonable understanding of the evaluation process and criteria. This paper describes a learning-oriented evaluation methodology and an open data framework that can be applied to collaborative project settings. An evaluation rubric and a series of indicators that provide evidences about the developed skills have been elaborated and applied in a small-scale project-based course. Projects were managed and developed with the help of an open source software forge that contains a ticketing tool for planning and tracking of tasks, a version control repository to save the software outcomes, and using a wiki to host text deliverables. The experience provides evidences in favor of using the assessment method and open data framework to make teamwork evaluation more sustainable.